MANAJEMEN LAYANAN BIMBINGAN KONSELING DALAM KURIKULUM 2013 DI SMP NEGERI 2 MARIORIWAWO KABUPATEN SOPPENG - Hasmah Hasmah; Muh. Yunus; Ahmad Hasyim; Muh. Yahya (STKIP Pembangunan Indonesia Makassar, 2018)
The current study examines the management Guidance and Counseling services in the 2013 curriculum, with the aim (1) to find out the planning of counseling and guidance services in the 2013 curriculum in SMPN 2 Marioriwawo, Soppeng Regency, (2) to find out the implementation of Guidance and Counseling services in the 2013 curriculum SMP Negeri 2 Marioriwawo, Soppeng Regency, (3) to find out the evaluation of Guidance and Counseling services in the 2013 curriculum in Marioriwawo 2 Public Middle School, Soppeng Regency.This research is qualitative in nature. The data collection techniques of this research were carried out by interviews, observation, and documentation. Data analysis was carried out with qualitative analysis which included data collection, data education, data presentation and conclusion drawing. The data sources in this study were guidance and counseling teachers as the main informants, and supporting informants namely principals, vice principals, subject teachers, homeroom teachers, administrative staff, and students.The results showed that, 1) the planning of guidance and counseling services (BK) in the 2013 Curriculum at SMP Negeri 2 Marioriwawo, Soppeng Regency was carried out well because it began with determining service goals as an analysis of student needs as the foundation of character formation which included annual programs, semester programs, monthly programs, weekly programs, and daily programs; 2) Implementation of Guidance and Counseling Services (BK) in the 2013 Curriculum at SMPN 2 Marioriwawo Soppeng Regency is well implemented by implementing data collection services, coordination and supervision; and 3) Evaluation of Guidance and Counseling Services (BK) in the 2013 Curriculum at SMPN 2 Marioriwawo Soppeng Regency was also carried out well by referring to the fulfillment of the students’ needs in fostering the attitude of the nation's character, which includes evaluation of the implementation and year-end evaluation.